2016
DOI: 10.1152/japplphysiol.00944.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiovascular reflexes evoked by airway stimulation with allylisothiocyanate, capsaicin, and ATP in Sprague-Dawley rats

Abstract: Acute inhalation of airborne pollutants alters cardiovascular function and evidence suggests that pollutant-induced activation of airway sensory nerves via the gating of ion channels is critical to these systemic responses. Here, we have investigated the effect of capsaicin [transient receptor potential (TRP) vanilloid 1 (TRPV1) agonist], AITC [TRP ankyrin 1 (TRPA1) agonist], and ATP (P2X2/3 agonist) on bronchopulmonary sensory activity and cardiovascular responses of conscious Sprague-Dawley (SD) rats. Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 73 publications
(90 reference statements)
1
39
0
Order By: Relevance
“…; Hooper et al. ), and the distribution of spinal afferent neurons within the lung is unknown. Early studies indicated that tracheal afferent nerve fibers originated in the C1 and T1–T4 DRG (Dalsgaard and Lundberg ; Kummer et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…; Hooper et al. ), and the distribution of spinal afferent neurons within the lung is unknown. Early studies indicated that tracheal afferent nerve fibers originated in the C1 and T1–T4 DRG (Dalsgaard and Lundberg ; Kummer et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact role and function of spinal afferent neurons in the lung is still unknown. Previous studies have indicated pressor, depressor, and biphasic blood pressure responses to cardiopulmonary spinal afferent activation (Weaver 1977;Kostreva et al 1981;Wang et al 2003;Soukhova-O'Hare et al 2006;Hooper et al 2016). The differences in whether an excitatory or inhibitory blood pressure response was observed in these studies are likely due to the preparations and experimental protocols used.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…148,149 Activation of P2X2/3 receptors expressed on nociceptive airway sensory nerves causes cardiovascular reflexes in conscious rats via reflex modulation of the autonomic nervous system. 150 The responses to adenosine of the transplanted human heart show supersensitivity. Donor pretreatment with AMP-activated PK activator protects cardiac grafts from cold ischemia/reperfusion injury.…”
mentioning
confidence: 99%